2008
DOI: 10.1002/hep.22485
|View full text |Cite
|
Sign up to set email alerts
|

A mutation in the canalicular phospholipid transporter gene, ABCB4, is associated with cholestasis, ductopenia, and cirrhosis in adults†‡

Abstract: Cholestatic liver disease (CLD) is a major cause of progressive liver damage and liver failure. Several forms of biliary cirrhosis are caused by mutations in specific genes. We sought to identify a genetic defect in a family with CLD impossible to assign to a distinct pathogenic entity. Clinical and histopathological characterization of the family members, microarraybased single-nucleotide polymorphism genotyping, and analysis of candidate genes were performed. Among six of 11 siblings severely affected by idi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
2
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(84 citation statements)
references
References 36 publications
2
79
2
1
Order By: Relevance
“…The p.(L481R) mutation was identified in three out of seven affected siblings belonging to family A, whereas the already characterized p.(Y403H) mutation 6,14 was identified in four affected members belonging to other two families. According to what is generally described, [13][14][15] the genotypes reported here show that (i) two mutant ABCB4 alleles are associated with severe early-onset of intrahepatic cholestasis characterized by a rapid course toward terminal liver failure. In particular, the infant bearing the homozygous p.(Y403H) mutation was diagnosed as PFIC-3 at the age of 3 months, and at the age of 3 years presented compensated cirrhosis with portal hypertension; (ii) a single mutant allele can be associated with hepatobiliary diseases with less significant and highly variable clinical features.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…The p.(L481R) mutation was identified in three out of seven affected siblings belonging to family A, whereas the already characterized p.(Y403H) mutation 6,14 was identified in four affected members belonging to other two families. According to what is generally described, [13][14][15] the genotypes reported here show that (i) two mutant ABCB4 alleles are associated with severe early-onset of intrahepatic cholestasis characterized by a rapid course toward terminal liver failure. In particular, the infant bearing the homozygous p.(Y403H) mutation was diagnosed as PFIC-3 at the age of 3 months, and at the age of 3 years presented compensated cirrhosis with portal hypertension; (ii) a single mutant allele can be associated with hepatobiliary diseases with less significant and highly variable clinical features.…”
Section: Discussionsupporting
confidence: 67%
“…10 In the following years, a growing number of ABCB4 mutations have been identified also in adult subjects affected by juvenile cholelithiasis, 11 drug-induced cholestasis 12 and idiopathic cholestasis of the adulthood. 13 Recently, our group highlighted that the simple heterozygous ABCB4 genotype could be a discrete risk factor for a wide range of hepatobiliary diseases, including the PFIC-3 phenotype with variable disease expressivity, 14 primary biliary cirrhosis and primary sclerosing cholangitis (Crosignani A, personal communication). To date, 146 disease-associated ABCB4 mutations are reported in the Human Genome Mutation Database (http://www.hgmd.org/; release date 14 December 2012); of them, 87 (about 60%) are predicted to substitute a single amino acid and 30 of these (about 34%) fall within the N-terminal NBD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduced expression of MDR3 reduces lecithin secretion and elevates vesicle cholesterol. It can also lead to bile duct damage, gallstone deposition, inflammation and biliary liver lesions (30)(31)(32).…”
Section: Groupmentioning
confidence: 99%
“…It has been suggested that confirmatory ERC after MRC should only be considered for cases in which the clinical findings are inconsistent with the diagnosis of PSC, such as cases involving underlying cirrhosis, cases in which the clinical suspicion is moderately high and cases with negative MRC results [8]. Therefore, in patients with unclear cholestasis, an ERC might be indicated to firmly exclude PSC and/or to obtain specimens for further analysis [4,9]. The detection of dominant strictures is of major importance because endoscopic treatment of these strictures is aimed to relieve biliary obstruction and to improve prognosis.…”
Section: Diagnosismentioning
confidence: 99%